INTEGRASI BUDIDAYA IKAN PATIN (Pangasius hypophthalmus) DAN TANAMAN AIR PADA PEMELIHARAAN SISTEM AKUAPONIK - muarofah ghofur; Nur Rizki; Muhammad Sugihartono (Jurnal Akuakultur Sungai dan Danau, 2021)
The purpose of this study is to find out whether the integration of catfish cultivation (P. hypophthalmus) and aquatic plants in the maintenance of aquaponic systems in order to produce high fish survival. The research was conducted using a Complete RandomIzed Design (RAL) environmental design with 4 (four) treatments and 3 (three) replays, each of these treatments is :P A behavior: 10 plant stems / holes and 2 fish / liter, Treatment B : 10 plant stems / holes and 3 fish / liters, Treatment C : 10 plant stems / holes and 4 fish / liter, Treatment D : 10 plant stems / holes and 5 fish / liter. The observed parameters are survival, growth and measurement of water quality. The results showed that the survival rate of catfish was 85.18%, 2.38 cm for length gain and weight gain of 2.80 g